Caracterização de células vermelhas por microscopia de força atômica - Costa, Erivelton Façanha da (2006)
The optical microscopy is the most employed technique used for visualize red blood cells (RBCs). But, due to its resolution limit, it is necessary to use other complementary techniques to study the cells, such as: the scanning and transmission electron microscopy, and the scanning probing microscopy. The Atomic Force Microscopy (AFM) is included in the last group. This work refers to the possibilities of using AFM in life science, focusing on the erythrocytes characterization. Five experiments involving red blood cells and AFM were carried out: AB+ and O+ blood types differentiation; RBCs membrane study of donors and patients with MDS (Myelodysplastic Syndrome); suitable preparation of red blood cells for AFM analysis; volume study of erythrocytes; and finally aging process observation of RBC in air. The first experiment determined the cell membrane roughness for AB+ and O+ groups, which were different. For the second one, depressions were found on the cell surface of both MSD patients and healthy people. These "holes" were deeper in the first group. The third experiment showed the importance of sample (RBCs) preparation for each AFM specific analysis. The fourth experimental procedure showed the AFM technique capability for providing volume information, which was also used in the last experiment to monitor the aging process of RBCs in air.